2016
DOI: 10.17116/stomat201695427-30
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy in treatment of severe oral lichen planus

Abstract: The aim of the study was to elaborate the rationale for the application of photodynamic therapy in complex treatment of patient with severe oral lichen planus. Complex clinical and laboratory examination and treatment was performed in 54 patients divided on 3 groups. Diagnosis of oral lichen planus was based on clinical, histological and immunohistochemical features. Group 1 received standard treatment, in the second group photodynamic therapy was conducted in addition to conventional treatment, patients in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Photodynamic therapy as a noninvasive procedure is more frequently used for the treatment of leukoplakia and LP. [22][23][24][25][26][27] Maloth et al revealed that in their study, in the leukoplakia group, 17% of cases showed a complete response, 66% showed a partial response and 17% of the lesions did not respond to the treatment. In the LP group, 80% of the lesions showed a partial response and 20% did not respond.…”
Section: Discussionmentioning
confidence: 90%
“…Photodynamic therapy as a noninvasive procedure is more frequently used for the treatment of leukoplakia and LP. [22][23][24][25][26][27] Maloth et al revealed that in their study, in the leukoplakia group, 17% of cases showed a complete response, 66% showed a partial response and 17% of the lesions did not respond to the treatment. In the LP group, 80% of the lesions showed a partial response and 20% did not respond.…”
Section: Discussionmentioning
confidence: 90%